Development and innovation potential in the Slovene manufacturing industry: first analysis of an industrial innovation survey - Ulrike Bross; Knut Koschatzky; Peter Stanovnik (Fraunhofer-Institut für System- und Innovationsforschung ISI, 1999)
Focussing on the firms' internal innovation capabilities and the external co-operative links, it is the aim of the paper to describe the structural composition of Slovenian manufacturing firms with respect to their innovative activities, to analyse their innovative performance using input and output indicators, and to assess their networking intensity with the different actors in the innovation system. Altogether, not only quantitative factors related to innovation will be identified, but also the potential of innovations in industry will be evaluated. This leads to including "soft" or contextual factors as preconditions for realising such potentials. For this reason, an innovation survey has been carried out in Slovenia during October 1997 and early 1998, addressing manufacturing firms, business-related service firms and research institutes. The methodology and the questionnaires of the survey have been applied also to other European regions such as Baden, southeast Lower Saxony and Saxony (Germany), Alsace and Gironde (France), Stockholm (Sweden), Wales (UK), South Holland (Netherlands), Vienna (Austria), and Barcelona (Spain) (see for example Backhaus/Seidel 1997; Fritsch et al. 1996; Koschatzky/Traxel1997, Muller 1997). Taking into account these previous experiences in other regions and the knowledge of the Slovene situation, the design of the research has been carefully adapted to the transition context by a joint German-Slovene team. This paper concentrates on reporting results derived from the Slovenian manufacturing industry innovation survey. For comparative reasons, some references are made either to the Baden sampie or to the results derived for Saxony, a region in transition within the process of German unification.
urn:nbn:de:0011-px-455619
Keywords: 330; Industrielle Forschung; Innovation; Verarbeitendes Gewerbe; Slowenien